2017
DOI: 10.20961/prosidingsnfa.v2i0.16362
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Model Pembelajaran Berbasis Pedagogi Ignasian pada Mata Kuliah Termodinamika

Abstract: This research aims to improve academic ability and help students to be able to find the values of life that it is useful to become a whole person. This research is a research of learning that it was prepared by Ignatian compassion) . The evaluation is done with observing the improvement of academic ability and the invention of life values. Implementation of Ignatian pedagogy in thermodynamics course has been able to improve academic and non academic ability of the students. The academic achievement is indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Zubaidah, 2019). A similar study was also revealed that in a literature study on the application of robotics in STEM learning in basic education, considered to be able to involve students cognitively, behaviorally and emotionally so that it can affect student motivation (Aristawati & Budiyanto, 2017).…”
Section: Introductionmentioning
confidence: 72%
“…Zubaidah, 2019). A similar study was also revealed that in a literature study on the application of robotics in STEM learning in basic education, considered to be able to involve students cognitively, behaviorally and emotionally so that it can affect student motivation (Aristawati & Budiyanto, 2017).…”
Section: Introductionmentioning
confidence: 72%
“…When engaging in mathematics learning activities, it is crucial to understand that mathematics encompasses more than just identifying numbers and performing counting tasks. The field of mathematics has a wide range of applications and concepts (Aristawati & Budiyanto, 2017;Gumiandari et al, 2019). Within this educational arena, the learning activity that can be conducted takes the shape of a numerical matching exercise.…”
Section: Mathematic Learning Domainmentioning
confidence: 99%
“…Dilihat dari aspek psikologi belajar, pembelajaran berdasarkan masalah merupakan suatu proses perubahan tingkah laku berkat adanya pengalaman. Belajar bukanlah semata-mata proses menghafal sejumlah fakta, tetapi suatu proses interaksi secara sadar antara individu dengan lingkungan (Kurniawan & wahyuningsih, 2020). Oleh karena itu, guru harus mendorong peserta didik untuk terlibat dalam tugas-tugas berorientasi masalah melalui penerapan konsep dan fakta, serta membantu menyelidiki masalah autentik dari suatu materi.…”
Section: Pendahuluanunclassified